Lateral hypothalamic area orexin-A influence the firing activity of gastric distension-sensitive neurons and gastric motility in rats. (June 2016) - Hao, Heling; Luan, Xiao; Guo, Feifei; Sun, Xiangrong; Gong, Yanling; Xu, Luo
Abstract: The orexins system consists of two G-protein coupled receptors (the orexin-1 and the orexin-2 receptor) and two neuropeptides, orexin-A and orexin-B. Orexin-A is an excitatory neuropeptide that regulates arousal, wakefulness and appetite. Recent studies have shown that orexin-A may promote gastric motility. We aim to explore the effects of orexin-A on the gastric -distension (GD) sensitive neurons and gastric motility in the lateral hypothalamic area (LHA), and the possible regulation by the paraventricular nucleus (PVN). Extracellular single unit discharges were recorded and the gastric motility was monitored by administration of orexin-A into the LHA and electrical stimulation of the PVN. There were GD neurons in the LHA, and administration of orexin-A to the LHA could increase the firing rate of both GD-excitatory (GD-E) and GD-inhibited (GD-I) neurons. The gastric motility was significantly enhanced by injection of orexin-A into the LHA with a dose dependent manner, which could be completely abolished by pre-treatment with orexin-A receptor antagonist SB334867. Electrical stimulation of the PVN could significantly increase the firing rate of GD neurons responsive to orexin-A in the LHA as well as promote gastric motility of rats. However, those effects could be partly blocked by pre-treatment with SB334867 in the LHA. It is suggested that orexin-A plays an important role in promoting gastric motility via LHA. The PVN may be involved in regulation of LHA on gastric motility. Highlights: Orexin-A could modulate the activity of GD responsive neurons in LHA. Orexin-A administration to LHA dose-dependently increased gastric motility. Stimulating PVN could excite orexin-A-responsive GD neurons in LHA. The effects of orexin-A could be blocked by antagonist of orexin-A receptors.